Lack of support for bexarotene as a treatment for Alzheimer's disease. (January 2016) - O'Hare, Eugene; Jeggo, Ross; Kim, Eun-Mee; Barbour, Bridgeen; Walczak, Jean-Sebastien; Palmer, Philip; Lyons, Taylor; Page, Deaglan; Hanna, Donncha; Meara, Jolyon R.; Spanswick, David; Guo, Jian-Ping; et al.
Abstract: Bexarotene has been reported to reduce brain amyloid-β (Aβ) levels and to improve cognitive function in transgenic mouse models of Alzheimer's disease (AD). Four groups failed to fully replicate the primary results but the original authors claimed overall support for the general conclusions. Because of its potential clinical importance, the current work studied the effects of bexarotene using two animal species and highly relevant paradigms. Rats were tested for the ability of bexarotene to prevent changes induced by an Aβ challenge in the form intracerebroventricular (i.c.v) administration of 7PA2 conditioned medium (7PA2 CM) which contains high levels of Aβ species. Bexarotene had no effect on the long-term potentiation of evoked extracellular field excitatory postsynaptic potentials induced by i.c.v. 7PA2 CM. It also had no effect following subcutaneous administration of 2, 5, 10 and 15 mg/kg on behavioral/cognitive impairment using an alternating-lever cyclic-ratio schedule of operant responding in the rat. The effects of bexarotene were further tested using the APPSwFILon, PSEN1*M146L*L286V transgenic mouse model of AD, starting at the time Aβ deposits first begin to develop. Mice were sacrificed after 48 days of exposure to 100 mg bexarotene per day. No significant difference between test and control mice was found using a water-maze test, and no significant difference in the number of Aβ deposits in cerebral cortex, using two different antibodies, was apparent. These results question the potential efficacy of bexarotene for AD treatment, even if instigated in the preclinical period prior to the onset of cognitive deficits reported for human AD. This article is part of the Special Issue entitled 'Synaptopathy – from Biology to Therapy'. Highlights: Amyloid-β is a central endogenous pathogen in Alzheimer's disease (AD). Soluble Aβ oligomers are the major cause of synaptotoxicity/neurodegeneration in AD. Bexarotene administration has been proposed as a potential treatment for AD. Bexarotene administration had no effects on histology or electrophysiology. Bexarotene administration had no effects on Aβ-induced cognitive decline.